Relational Identity and Identification: Defining Ourselves Through Work Relationships - Sluss, David M.; Ashforth, Blake E. (Academy of Management Review, 2007)
We explore the meaning and significance of relational identity and relational identification, predicated on the role-relationship between two individuals. We argue that relational identity integrates person- and role-based identities and thereby the individual, interpersonal, and collective levels of self; contrast relational identity and relational identification with social identity and social identification; contend that relational identity and relational identification are each arranged in a cognitive hierarchy ranging from generalized to particularized schemas; and contrast relational identification with relational disidentification and ambivalent relational identification.